Integrating Prevention of Pregnancy Complaints and Mental Health Promotion in Antenatal Care: Midwives’ View - Asih, Fransisca Retno; Winarna, Nuristy Brillian Ainindyahsari; Danti, Renita Rizkya (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
Physiological and psychological changes during pregnancy can cause various complaints, such as nausea, back pain, and sleep disturbances, as well as increase the risk of mental health disorders such as anxiety and depression. However, current antenatal services still focus more on physical aspects compared to preventing pregnancy complaints and promoting mental health. This study aims to explore the integration of education on preventing common pregnancy complaints and promoting mental health in first contact antenatal care based on the perspective of midwives. The research method used was qualitative with purposive sampling technique, involving 6 midwives as participants, conducted for 4 months, and analyzed using thematic analysis. The results of the study identified six main themes, including low coverage of first pregnancy contact (K1), suboptimal mental health education, and the need for service integration and the use of digital-based educational media. The conclusion of this study confirms that improving the quality of antenatal services requires revision of procedures, innovation in digital education, and stronger social support to improve the welfare of pregnant women.